Strategi Perencanaan Peserta Didik di SDS Terpadu Bina Ilmu: Upaya Meningkatkan Kualitas Pendidikan Holistik - Damanhuri, Faiz Madani; Mujahidin, Endin; Andriana, Nesia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines student planning strategies at SDS Terpadu Bina Ilmu as an effort to improve holistic education quality. Holistic education integrates intellectual, emotional, and spiritual aspects of students through a curriculum that balances general and religious studies. This research employs a qualitative approach using library research methods. The findings reveal that student planning, encompassing needs analysis, recruitment, selection, orientation, placement, and reporting, plays a crucial role in creating an inclusive learning environment and optimizing students' potential. Through a holistic education approach, SDS Terpadu Bina Ilmu successfully produces high-achieving, well-rounded, and morally upright students aligned with its vision and mission. This study highlights the importance of collaboration among schools, educators, and parents to support the success of these planning strategies.